Analysis of The Application of PSAK 101 in The Presentation of Financial Statements of Bank Muamalat Indonesia: Sharia Accounting Perspective - Irza Faridz Muhammad; Fathonah Azzahra; Widia Sri Kartika Sari Manalu; Ridho Alkhalik; Yusnita Purba; Meigia Nidya Sari (International Journal of Economic Research and Financial Accounting, 2025)
This article discusses the application of the Statement of Financial Accounting Standards 101 in the presentation of Bank Muamalat Indonesia's financial statements from a sharia accounting perspective. The aim of this research is to analyze the extent to which Bank Muamalat Indonesia implements PSAK 101 in preparing its financial reports in accordance with applicable sharia principles. The method used in this research is a literature review which examines various literature sources related to PSAK 101, sharia accounting, and the implementation of sharia regulations in the Indonesian banking sector. The research results show that Bank Muamalat Indonesia has a strong commitment to sharia principles, by implementing the principles of justice and transparency in the products and services offered. The implementation of PSAK 101 by Bank Muamalat includes a strict evaluation of the conformity of each transaction with sharia provisions, although there are still challenges in integrating sharia regulations with the development of the modern banking industry. Thus, even though Bank Muamalat Indonesia has succeeded in implementing PSAK 101 well, continuous policy updates are still needed so that it remains in line with applicable regulations and developments in the sharia banking industry in Indonesia.